Antiretroviral choice and severe disease predict poorer neuropsychological outcomes in HIV+ children from Africa - Fairlie, Lee; Chernoff, Miriam; Cotton, Mark F.; Bwakura-Dangarembizi, Mutsa; Violari, Avy; Familiar-Lopez, Itziar; Barlow-Mosha, Linda; Kamthunzi, Portia; McCarthy, Katie; Jean-Philippe, Patrick; Laughton, Barbara; Palumbo, Paul E.; et al. (Frontiers in Pediatrics, 2022)
Background: The International Maternal Pediatric Adolescent AIDS Clinical Trials Network (IMPAACT) P1104s study evaluated neuropsychological outcomes over 96 weeks in children living with HIV (CLHIV) aged 5 to 11 years at 6 Sub-Saharan African sites to explore associations between HIV-illness related biomarkers and neuropsychological outcomes. Methods: CLHIV had participated in IMPAACT P1060, which compared efficacy of nevirapine versus lopinavir/ritonavir in children initiating ART at < 3 years of age. At age 5-11, neuropsychological evaluations of KABC cognitive ability, TOVA attention-impulsivity and BOT-2 motor domains were assessed and repeated after 48 and 96 weeks. Clinical, antiretroviral therapy (ART) and laboratory (immunological and virological) parameters were used to predict neuropsychological outcomes using linear mixed-effects multivariable regression models, controlling for child and caregiver characteristics. Results: 246 CLHIV (45% male, mean age at initial neuropsychological evaluation 7.1 yrs [SD 1.2]) began ART at a median age at 14.9 months (IQR 8.2, 25.2). Nadir CD4 percentage was 14.7% (IQR 11.0, 19.5); the median peak viral load (VL) was 750 000 copies/ml (IQR 366 000, 750 000) and 63% had ≥ WHO stage 3 clinical ¬disease; 164 (67%) were on lopinavir/ritonavir, 71 (29%) were on nevirapine and 7 (3%) were on efavirenz. Other antiretrovirals were similar. Nevirapine at P1104s study start or later was associated with poorer neuropsychological scores across all domains except Global Executive Composite, even when controlling for nadir CD4 percent and time-varying HIV VL. Other predictors of poorer scores in KABC domains included low birth weight, WHO stage 4 disease and serious illness history and elevated VL was associated with worse BOT-2 scores. Conclusions: Children receiving nevirapine had poorer neuropsychological scores than those on lopinavir/ritonavir. Antiretroviral choice might adversely impact neuropsychological performance. In addition, low birth weight and markers of severe HIV disease: advanced WHO clinical HIV disease, history of serious illness and an elevated VL, were associated with lower neuropsychological scores.